2015
DOI: 10.1158/1535-7163.mct-14-0865
|View full text |Cite
|
Sign up to set email alerts
|

The TMPRSS2–ERG Gene Fusion Blocks XRCC4-Mediated Nonhomologous End-Joining Repair and Radiosensitizes Prostate Cancer Cells to PARP Inhibition

Abstract: Exposure to genotoxic agents, such as ionizing radiation (IR) produces DNA damage leading to DNA double-strand breaks (DSBs); IR toxicity is augmented when the DNA repair is impaired. We reported that radiosensitization by a PARP inhibitor (PARPi) was highly prominent in prostate cancer (PCa) cells expressing the TMPRSS2-ERG gene fusion protein. Here, we show that TMPRSS2-ERG blocks non-homologous end-joining (NHEJ) DNA repair by inhibiting DNA-PKcs. VCaP cells, which harbor TMPRSS2-ERG and PC3 cells that stab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
(79 reference statements)
2
27
0
Order By: Relevance
“…Intriguingly, however, those Ligase IV−/− cells, but not the normal cells, were also p53−/−, due to the inviability of p53+/+ Ligase IV−/− mice, whereas HCT116 and its derivatives are p53+/+. An alternative explanation for the relative lack of sensitization of the Ligase IV−/− HCT116 cells is that these cells, after extended propagation in culture, have acquired upregulated HRR or Alt-NHEJ functions [79], rendering these repair systems less susceptible to PARP inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, however, those Ligase IV−/− cells, but not the normal cells, were also p53−/−, due to the inviability of p53+/+ Ligase IV−/− mice, whereas HCT116 and its derivatives are p53+/+. An alternative explanation for the relative lack of sensitization of the Ligase IV−/− HCT116 cells is that these cells, after extended propagation in culture, have acquired upregulated HRR or Alt-NHEJ functions [79], rendering these repair systems less susceptible to PARP inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a newly published in vivo study reported that prostate tumour cells carried TMPRSS2-ERG gene fusion, the most common genetic aberration, which is found in approximately 50% of patients with PCa [126,127]. That means an impaired D-NHEJ repair pathway by inhibiting DNA-PKcs and enhancing the PARP inhibitor-mediated radiosensitization [128]. Furthermore, TMPRSS2-ERG expressing tumour cells have elevated levels Rad51 foci and HR activity after IR, indicating an HR compensatory effect for the defective D-NHEJ and the plausible synthetic lethal interaction that may exert between TMPRSS2-ERG expressing tumour cells and PARP inhibitors [128].…”
Section: Discussionmentioning
confidence: 99%
“…That means an impaired D-NHEJ repair pathway by inhibiting DNA-PKcs and enhancing the PARP inhibitor-mediated radiosensitization [128]. Furthermore, TMPRSS2-ERG expressing tumour cells have elevated levels Rad51 foci and HR activity after IR, indicating an HR compensatory effect for the defective D-NHEJ and the plausible synthetic lethal interaction that may exert between TMPRSS2-ERG expressing tumour cells and PARP inhibitors [128]. We hypothesised that PARP-mediated B-NHEJ will gain a more predominant roll in IR-induced DSBs repair following castration and combined treatment of ADT and PARP inhibitor leads to synthetically lethal effect in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…While therapeutic targeting of transcription factor oncogenes is intrinsically challenging, on the basis of the interaction of ERG with the DNA repair enzyme PARP1 and DNA protein kinase DNA-PKc, use of PARP inhibitors was shown to inhibit growth of TMPRSS2-ERG -positive prostate cancer xenografts [ 145 ]. Additionally, PARP inhibition was associated with radiosensitization of TMPRSS2 - ERG -positive prostate cancer cells [ 146 , 147 ]. These experimental leads point to possible therapeutic avenues targeting a prevalent gene fusion in a common carcinoma.…”
Section: Gene Fusion Signatures In Personalized Medicine Of Epitheliamentioning
confidence: 99%